Իսլամը արաբական Արմինիյայում - Շահինյան, Արսեն («Նաիրի» հրատ.)
At the beginning of the 8th century the lands of Greater Armenia as well as the lands of Caucasian Iberia (K‗art‗li) and Albania (Ałuank‗) conquered by the Muslims were included into the administrative unit (Arab. vilayet) of the Arab Caliphate named Arminiya. In academic literature, it is accepted to write that at the early stage of the conquests the Arabs-Muslims were tolerant of other creeds. They really were, although in the 8th century it is impossible to find in Armenian or Georgian sources information about construction of new churches on the territory of Arminiya while the whole preceding period in Christian history of Armenia, Iberia and Albania (4th -7 th centuries) was marked with a boom of building such religious facilities. Moreover, in the very centre of the largest cities of Arminiya, often in close proximity to an ancient church, cathedral mosques began to tower. This fact was acknowledged by Arab and Persian geographers and travelers of the 10th century who would visit this northern region
Keywords: Իսլամ; Արաբական երկրներ